Application of multi-antenna technology based on the indoor scene - Chongyang LI; Guoan HU; Boyong FAN; Yongping ZHU (Dianxin kexue)
Multi-antenna technology is the key technology of high speed broadband wireless access network,it has a broad application prospect in the fourth generation mobile communication systems.Indoor coverage is the main business for mobile communication.It is very important to use the MIMO technology to solve the problem of indoor wireless communication.Focused on the theme of wireless MIMO technology in the indoor coverage,MIMO channel capacity,indoor channel modeling,indoor coverage systems were mainly analyzed.